Doping risk and career turning points in male elite road cycling (2005-2016) - Aubel, O.; Lefèvre, B.; Le Goff, J. M.; Taverna, N. (Journal of Science and Medicine in Sport, 2018)
Objectives: Determine whether career paths of elite male professional riders explain the risk of being sanctioned for an Anti-Doping Rules Violation through the International Cycling Union. Design, methods: A discrete-time logit model explored the link between career path and ADRV risk in a database of 10,551 riders engaged in the first three world divisions (2005-2016), including 271 sanctioned riders. Results: Despite a longer career (7.8 years), sanctioned riders have a precarious path. The odds of finding a sanctioned rider within those who experienced a career interruption is 5.80 times higher than for a non-caught one. 61% of the caught riders have experienced a team change. The odds of finding a caught rider within those who experienced such a change is 1.35 times higher. 44% of caught riders start before 23 years, vs 34% for non-sanctioned ones. The odds of being sanctioned are 1.69 times higher for doped riders beginning before 23. The odds of finding a sanctioned rider are 1.94 times higher among those starting their careers before 2005 (establishment of Pro Tour), than those who started in 2008 or after. In that year, the Cycling Anti-Doping Foundation and the biologic passport were both launched. Conclusions: Caught riders could have extended their more precarious careers with doping. The post-2005 generation effect could mean that riders are cleaner or slicker at hiding doping. The higher risk of being caught for riders starting after 23 might indicate that an early professional socialization reduces the risk by teaching them to be cleaner, or better at hiding doping.